Application of THEKA: Synthetic Substitute Dura, in Animal Study: Preliminary Report - Patamatham, Sadudee; Hemstapat, Warinkarn; Suwanprateeb, Jintamai; Chumnanvej, Sorayouth (Thai Journal of Neurological Surgery, 2025)